Potential health risk of endocrine disruptors in construction sector and plastics industry: a new paradigm in occupational health - Fucic, Aleksandra (2018)
Endocrine disruptors (EDs) belong to large and diverse groups of agents that may cause multiple biological effects associated with, for example, hormone imbalance and infertility, chronic diseases such as diabetes, genome damage and cancer. The health risks related with the exposure to EDs are typically underestimated, less well characterized, and not regulated to the same extent as, for example, carcinogens. The increased production and utilization of identified or suspected EDs in many different technological processes raises new challenges with respect to occupational exposure settings and associated health risks. Due to the specific profile of health risk, occupational exposure to EDs demands a new paradigm in health risk assessment, redefinition of exposure assessment, new effects biomarkers for occupational health surveillance and definition of limit values. The construction and plastics industries are among the strongest economic sectors, employing millions of workers globally. They also use large quantities of chemicals that are known or suspected EDs. Focusing on these two industries, this short communication discusses: (a) why occupational exposure to EDs needs a more specific approach to occupational health risk assessments, (b) identifies the current knowledge gaps, and (c) identifies and gives a rationale for a future occupational health paradigm, which will include ED biomarkers as a relevant parameter in occupational health risk assessment, surveillance and exposure prevention